An epidermal patch for the simultaneous monitoring of haemodynamic and metabolic biomarkers - Sempionatto, J. R.; Lin, M.; Yin, L.; De la paz, E.; Pei, K.; Sonsa-ard, T.; de Loyola Silva, A. N.; Khorshed, A. A.; Zhang, F.; Tostado, N.; Xu, S.; Wang, J. (Nature Biomedical Engineering, 2021)
Monitoring the effects of daily activities on the physiological responses of the body calls for wearable devices that can simultaneously track metabolic and haemodynamic parameters. Here we describe a non-invasive skin-worn device for the simultaneous monitoring of blood pressure and heart rate via ultrasonic transducers and of multiple biomarkers via electrochemical sensors. We optimized the integrated device so that it provides mechanical resiliency and flexibility while conforming to curved skin surfaces, and to ensure reliable sensing of glucose in interstitial fluid and of lactate, caffeine and alcohol in sweat, without crosstalk between the individual sensors. In human volunteers, the device captured physiological effects of food intake and exercise, in particular the production of glucose after food digestion, the consumption of glucose via glycolysis, and increases in blood pressure and heart rate compensating for oxygen depletion and lactate generation. Continuous and simultaneous acoustic and electrochemical sensing via integrated wearable devices should enrich the understanding of the body`s response to daily activities, and could facilitate the early prediction of abnormal physiological changes.